2019
DOI: 10.3390/beverages5030049
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Storage at Room Temperature for Fruit Juice Preservation

Abstract: Hyperbaric storage is an innovative preservation method that consists of storing food under pressure, either at room or at low temperature, for time periods of days, weeks, or months. Recent scientific literature shows that hyperbaric storage at room temperature (HS-RT) could be an efficient method for fruit juice preservation. Depending on the level applied, pressure can inhibit and even inactivate the endogenous microflora of the fresh juice, while properly preserving other organoleptic and quality indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Moreover, to minimize pressure-induced quality losses, pressure should be set to the minimum level required to prevent microbial growth in the product during storage. This pressure depends not only on the storage temperature, but also on some intrinsic food characteristics such as its composition, water activity, or pH, among others (Otero 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to minimize pressure-induced quality losses, pressure should be set to the minimum level required to prevent microbial growth in the product during storage. This pressure depends not only on the storage temperature, but also on some intrinsic food characteristics such as its composition, water activity, or pH, among others (Otero 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the storage with low pressure at room temperature can be an effective technique to fruit and vegetable juices' storage, as pressure inhibits the microbial content of fresh juice, besides enhancing sensory characteristics and the quality of the juice. Reports indicated that low-pressure storage prolonged vegetable and fruit juices' shelf life; it also reduced energy costs more than refrigeration storage [15][16][17][18]. Lemos et al [19] preserved watermelon juice with low pressure , at room temperature, for two months.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease may be associated with the breakdown of pectic substances and an increase in total soluble solids. Otero, (2019) reported that an increase in viscosity may affect mouthfeel. Nonetheless, the decreasing pattern was also linked with the findings of Rashid et al (2018).…”
Section: Effect Of Sodium Alginate Beads and Storage On Titratable Ac...mentioning
confidence: 99%
“…However, a comparable decline was found in T1 and T3 from 7.83 to 7.19 and 7.83 to 6.5 respectively. According to Otero, (2019) this decreasing trend was due to physicochemical reactions and sodium alginate beads present in the juice. However, flavour score may decrease due to caramelization and fermentation (Bal et al, 2014).…”
Section: Figure 3: Effect Of Probiotics On the Mouthfeel Of Guava Jui...mentioning
confidence: 99%